A Meta-Analytic Review of Obesity Prevention Programs for Children and Adolescents The Skinny on Interventions That Work. [article]. - Stice, Eric
This meta-analytic review summarizes obesity prevention programs and their effects and investigates participant, intervention, delivery, and design features associated with larger effects. A literature search identified 64 prevention programs seeking to produce weight gain prevention effects, of which 21% produced significant prevention effects that were typically pre-to post effects. Larger effects emerged for program that targeted children and adolescents (vs. pre-adolescents) and females, programs that were relatively brief, program that solely targeted weight control versus other health behaviors (e. g.,smoking), programs evaluated in pilot trials, and programs wherein participants must have self-selected into the intervention. Other factors, including mandated improvements in diet and exercise, sedentary behavior reduction, delivery by trained interventionists, and parental involvement, were not associated with significantly larger effects. . -- (from the author)
Keywords: Obesity; Prevention; Meta-analysis.; Moderators